Students’ Error In Pronouncing English Vowel - Dimas Dimas; Yulia Hidayat; Yani Lubis (Lembaga Pengembangan Kinerja Dosen, 2023)
Language and how to pronounce it are inseparable in the context of learning a new language. There are undoubtedly faults in the process of pronouncing a word in any language, particularly non-native languages. While many people confuse error with a mistake, error often refers to the difference between the actual or expected value and the resultant or observed value. Errors may be measured, examined, and used to determine the degree of correctness or inaccuracy in a variety of domains. Mistakes, on the other hand, are more typically seen in general or daily conditions. Mistakes are often defined as improper or wrong behaviors or decisions, whether in decision-making, physical activities, or communication. Incomprehension, carelessness, or actions that are contrary to what should have been done are all examples of mistakes. This study, which focused on the pronunciation errors produced by English language education majors at the college of education, employed a qualitative descriptive approach to gather information from 20 students and ask them to read a short tale. This study identified three types of error: Substitution, additional, and omission. Following additional with 3.78% and omission with 0.34% as the least frequent error types made by students, it was discovered after gathering all the data that substitution accounted for 100% of all errors.